Economic Consequences of Brexit : The impact on the ICT sector in Ireland - Bracken, Conor; Čajka, Radek, 1983-; Coniglio, Nicola Daniele; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The thesis examines the potential impact that the United Kingdom's exit from the European Union on the Irish Information & Communications Technology Sector. Ireland's economic success over the past several decades is exemplified in its place as an investment hub for a litany of Technological Multinationals. EU membership, English speaking population and Industrial Policy have been instrumental in this development. Brexit, however, poses enormous risks for the sector given Ireland's close relationship with the United Kingdom. The thesis explores both the potential opportunities that the Brexit vote poses while also bringing to light the many threats born out of this development. The study examines this potential consequences by way of comparison, highlighting how Brexit will impact upon Data Protection, migration flows and investment. Several economic theories underpin the work such as the Gravity Model, first-mover advantage and agglomeration and clustering forces.
Vedoucí práce: Radek Čajka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses